2016
DOI: 10.1016/j.jenvrad.2016.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Thirty years after the Chernobyl accident: What lessons have we learnt?

Abstract: April 2016 sees the 30(th) anniversary of the accident at the Chernobyl nuclear power plant. As a consequence of the accident populations were relocated in Belarus, Russia and Ukraine and remedial measures were put in place to reduce the entry of contaminants (primarily (134+137)Cs) into the human food chain in a number of countries throughout Europe. Remedial measures are still today in place in a number of countries, and areas of the former Soviet Union remain abandoned. The Chernobyl accident led to a large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
84
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(88 citation statements)
references
References 137 publications
0
84
0
4
Order By: Relevance
“…reported that children consuming fungi showed a high 137 Cs body burden near the plant16. It is well known that after the accident at the Chernobyl Nuclear Power Plant, wild fungi could be an important contributor to 137 Cs body burdens, due to their capacity to accumulate 137 Cs, and that certain population groups showed relatively high internal exposure due to intakes of such foodstuffs17. Since the accident at FDNPS, decontamination in the forests beyond a 20-m radius from residential houses has not been conducted10, leading to the relatively high concentrations of radiocesium in edible wild plants and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…reported that children consuming fungi showed a high 137 Cs body burden near the plant16. It is well known that after the accident at the Chernobyl Nuclear Power Plant, wild fungi could be an important contributor to 137 Cs body burdens, due to their capacity to accumulate 137 Cs, and that certain population groups showed relatively high internal exposure due to intakes of such foodstuffs17. Since the accident at FDNPS, decontamination in the forests beyond a 20-m radius from residential houses has not been conducted10, leading to the relatively high concentrations of radiocesium in edible wild plants and fungi.…”
Section: Discussionmentioning
confidence: 99%
“…These larger fragments were predominantly deposited at a distance of 2-5 km from the reactor (Kashparov et al, 1999). The deposition of particles was a distinguishing feature of radioactive contamination of the Chernobyl accident and the behaviour of radionuclides associated with such particles in the environment had not previously been considered (Loshchilov et al, 1991;Beresford et al, 2016).…”
Section: Hot or Fuel Particlesmentioning
confidence: 99%
“…-The presence of radioactive particles means that their behaviour in the environment can be studied (Kashparov et al, 1999;Beresford et al, 2016). Fuel particles (FPs) are weathered with time such that mobilisation of 90 Sr has been observed to lead to increased contamination of plants (Salbu et al, 1994;Oughton et al, 1993;Kashparov et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…A series of rodent studies in highly contaminated sites (average dose up to 830 mGy/h) showed no clear evidence of genetic changes compared to control sites (Baker et al 2001;Wickliffe et al 2002). However, a study in Belarus which experienced lower dose rates (up to 30 mGy/day) showed increased frequency of chromosome aberrations (Goncharova and Ryabokon 1995;Beresford et al 2016). …”
Section: The Chernobyl Nuclear Accidentmentioning
confidence: 99%
“…Prior to the Chernobyl accident, mammals were perceived to be among the most radiosensitive taxonomic groups (Geras'kin et al 2008;Beresford et al 2016). A series of rodent studies in highly contaminated sites (average dose up to 830 mGy/h) showed no clear evidence of genetic changes compared to control sites (Baker et al 2001;Wickliffe et al 2002).…”
Section: The Chernobyl Nuclear Accidentmentioning
confidence: 99%